Collision of malignant neoplasms of the skin: basosquamous cell carcinoma associated with melanoma - Paula Mota Medeiros; Natália Ribeiro de Magalhães Alves; Cássia Camarinha da Silva; Paula Carolina Pessanha de Faria; Carlos Baptista Barcaui; Juan Piñeiro-Maceira (Sociedade Brasileira de Dermatologia, 2015)
AbstractCollision tumors are characterized by the coexistence of two cancers in the same anatomical site and its pathogenesis remains controversial. Although uncommon, the association of basal cell carcinoma and melanocytic nevus is the most common among combinations of skin tumors. Even rarer is the association of two malignant tumors. We report a case of tumor collision representing melanoma and basosquamous cell carcinoma, a combination not previously described in the literature, since there are no reported cases of melanoma with this type of basal cell carcinoma.